USE OF GARLIC (Allium sativum) IN FRESH DUMBO CATFISH (Clarias gariepinus) ON THE QUALITY OF ORGANOLEPTIC AND MICROBIOLOGICAL DURING CHILLED STORAGE - Nurul Huda; N. Ira Sari; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine the effect of the use of garlic (Allium sativum) on organoleptic and microbiological quality in dumbo catfish (Clarias gariepinus) during chilled storage. The treatment in this study was the concentration of garlic at a level of 0, 10, 15 and 20% with retention period of 0, 3, 6, 9 days. The test parameters performed included organoleptic, TPC, and Escherichia coli tests with non-factorial completely randomized design (CRD). The results showed that the use of garlic had significantly affected the characteristic of organoleptic quality (eyes, gills, texture and odor) and microbiological in catfish during cold storage. The use of 20% garlic  preserved the organoleptic quality of the eyes, texture, and odor for 6 days of storage. Meanwhile, the use of 20% garlic  reduced the number of microbes for 9 days of storage. Key words:Dumbo catfish, garlic, organoleptic quality, TPC.